Strategi Collaborative Learning dalam Pelaksanaan Pembelajaran Sosiologi pada Kurikulum Merdeka di Kelas XI IPS MAN 1 Pontianak - Wulandari, Desi; Asriati, Nuraini; Ramadhan, Iwan (Daya Nasional: Jurnal Pendidikan Ilmu-Ilmu Sosial dan Humaniora, 2025)
This study aims to analyze the Collaborative Learning strategy in the implementation of sociology learning in the Merdeka Curriculum in class XI IPS MAN 1 Pontianak. The background of this study is based on the dominance of monotonous and teacher-centered learning methods, resulting in suboptimal student engagement. Collaborative Learning is considered important because it can create an interactive learning atmosphere, foster cooperation, and train students' critical thinking skills. This study employs a qualitative method with a descriptive approach. The research subjects were determined through purposive sampling, involving a sociology teacher and three students, while data was collected through observation, interviews, and documentation. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing, with data validity tested through source and technique triangulation. The results of the study indicate that Collaborative Learning is implemented through systematic planning, including the preparation of teaching modules, selection of materials, supporting media in the form of QuizWhizzer, and division into discussion groups. The implementation of this strategy generated positive responses from students in terms of cognitive, affective, and interactive aspects, as seen from their enthusiasm in discussions and an average quiz score of 88. The challenges faced included limited internet access and devices, but these did not diminish the effectiveness of the learning process. The conclusion of this study is that Collaborative Learning can be an effective strategy in supporting the implementation of the Merdeka Curriculum because it enhances student activity, cooperation, and learning outcomes in the subject of Sociology.